On the Modified q-Bernoulli Numbers of Higher Order with Weight - T. Kim; J. Choi; Y.-H. Kim; S.-H. Rim (Abstract and Applied Analysis)
The purpose of this paper is to give some properties of the modified q-Bernoulli numbers and polynomials of higher order with weight. In particular, by using the bosonic p-adic q-integral on ℤp, we derive new identities of q-Bernoulli numbers and polynomials with weight.